Biomechanical Forces Regulate Gene Transcription During Stretch-Mediated Growth of Mammalian Neurons - Loverde, Joseph R.; Tolentino, Rosa E.; Soteropoulos, Patricia; Pfister, Bryan J. (Frontiers in Neuroscience, 2020)
At birth, there are 100 billion neurons in the human brain, with functional neural circuits extending through the spine to the epidermis of the feet and toes. Following birth, limbs and vertebrae continue to grow by several orders of magnitude, forcing established axons to grow by up to 100 cm in length without motile growth cones. The leading regulatory paradigm suggests that biomechanical expansion of mitotic tissue exerts tensile force on integrated nervous tissue, which synchronizes ongoing growth of spanning axons. Here, we identify unique transcriptional changes in embryonic rat DRG and cortical neurons while the corresponding axons undergo physiological levels of controlled mechanical stretch in vitro. Using bioreactors containing cultured neurons, we recapitulated the peak biomechanical increase in embryonic rat crown-rump-length. Biologically paired sham and ‘stretch-grown’ DRG neurons spanned 4.6- and 17.2-mm in length following static or stretch-induced growth conditions, respectively, which was associated with 456 significant changes in gene transcription identified by genome-wide cDNA microarrays. Eight significant genes found in DRG were cross-validated in stretch-grown cortical neurons by qRT-PCR, which included upregulation of Gpat3, Crem, Hmox1, Hpse, Mt1a, Nefm, Sprr1b, and downregulation of Nrep. The results herein establish a link between biomechanics and gene transcription in mammalian neurons, which elucidates the mechanism underlying long-term growth of axons, and provides a basis for new research in therapeutic axon regeneration.